臺北市國小資源班學生個別化教育計畫設計及執行情形之研究 Design and Implementation of Individualized Education Plans for Elementary Students with Disabilities Who Participate in Resource Programs in Taipei City - 柯懿真 Yi-Zhen Ke; 盧台華 Tai-Hwa Emily Lu (National Changhua University of Education, 2019)
本研究目的在檢視臺北市國小資源班學生個別化教育計畫設計與執行情形。由研究者與五名評定者以自編之「個別化教育計畫評鑑檢核表」評鑑72 名資源班學生103 與104 學年度之IEP。主要發現有： 1.85% 以上之IEP 均能具備特教法令規範之基本要項，且與學生之需求達到適配性。 2. 兩年度之IEP 設計與執行情形較理想之向度為「行政管理與執行」。待改善之處包括評量記錄多為一年以上的資料；較少敘明學生所需之教學和評量調整內容；部分學習領域之學習節數無法與學年教育目標配合；教育目標之可測量性/ 可觀察性、類化性、可行性等待改善；相關專業服務、行為功能介入方案說明不完整，且轉銜服務多以六年級學生為主。 The main purpose of this study was to evaluate the contents and qualities of Individualized Educational Plans (IEPs) of elementary students with disabilities in Taipei City. The researcher and five co-raters employed a self-designed "IEP Evaluation Checklist" to analyze students' IEPs from 2014 to 2015, covering 72 elementary students with disabilities who had participated in resource programs. The main findings are as follows. 1. About 85% of "IEP-required content" met the requirements of the related special education laws and matched students' special needs. 2. The best area of quality rating from 2014 to 2015 was "administrative management and execution". The area needing improvement included stated assessment records of more than one year. However, there lacked adaptations of instructional designs and assessments. Moreover, the number of lessons of some areas/subjects provided did not match annual education goals; the qualities of the observability, generalization, and accessibility of goals/ objectives were in need of improvement; the contents of related services and behavior intervention programs of IEPs were not stated clearly; and IEPs were mainly developed for the 6 graders with transition needs.